Soviet-Norwegian relations : Norwegian reactions to Soviet pressures. - Devlin, Daniel Dale (1979)
This research provides an analysis of the current security threat to Norway posed by increased Soviet pressures on the northern flank of NATO and Norwegian reactions to Soviet pressure. Nordic regional security is discussed in order to determine the background of Norwegian NATO membership, Nordic unity and the importance of the northern flank. As Soviet pressures have increased in Norwegian territorial waters and airspace, on the Svalbard archipelago, and in the Barents and Norwegian seas, Norwegian support of NATO has been questioned, particularly regarding political trends in Norway in the early 1970' s and Norwegian policies concerning NATO. The results of the research determine that Soviet pressure has been counterproductive. Norwegian support for NATO has increased as a result of pressure. Other Norwegian national issues are not directly related to support for NATO, but are a result of regional unity and national interests. Approved for public release; distribution is unlimited. Captain, United States Army http://archive.org/details/sovietnorwegirel1094518870